Biomass-derived multiatom-doped carbon dots for the photocatalytic reduction of Cr(VI) and precipitation of Cr(III) - Gunture; Tae Yoon Lee (npj Clean Water)
Abstract The release of heavy metal ions, especially hexavalent chromium [Cr(VI)], from industrial processes poses significant health and environmental risks. Cr(VI) does not readily degrade but can be reduced to the less toxic trivalent form [Cr(III)] that exhibits lower adsorption, making it easier to manage and remove from environmental systems. This paper proposes a single-step solvothermal method to synthesize fluorescent multiatom-doped (N, K, Cl, Mg, and Ca) carbon dots (MACDs) from Kalanchoe pinnata leaves (carbon precursor) and ethanol (solvent). These MACDs serve as effective photocatalysts for Cr(VI) reduction under one sun illumination (AM 1.5 G conditions). The reaction achieved a 91% Cr(VI) removal from a 20 ppm deionized water solution in 420 min and complete removal (100%) in an acidic solution with the same initial concentration in 120 min. The MACDs demonstrated excellent photocatalytic performance across tap, river, and lake water. These biomass-derived MACDs demonstrate strong potential for effective Cr-contaminated water remediation.